RELATED VOCATIONAL INTEREST TO LEARNING AND ENTREPRENEURIAL LEARNING ACHIEVEMENT WITH ENTREPRENEURSHIP INTEREST ON THE STUDENS AUTOMOTIVE ENGINEERING ISLAMIC VOCATIONAL SCHOOL YOGYAKARTA ACADEMIC YEAR 2013/2014 - Choiruddin Nurcholis Suwondo; Subagyo Subagyo (Jurnal Taman Vokasi, 2014)
The purpose of the study (1) to determine whether there is a positive relationship between vocational interest to learning with entrepreneurship interest on the studens Automotive Engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014; (2) to determine whether there is a positive relationship between entrepreneurial learning achivement with entrepreneurship interest on the studens Automotive Engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014; (3) to determine whether there is a positive relationship between vocational interest to learning and entrepreneurial learning achivement with entrepreneurship interest on the studens automotive engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014 .This research was conducted at Islamic Vocational School Yogyakarta Academic Year 2013/2014. The population in this study were all students of class XI Automotive Engineering totaling 30 students and this study used a sampling saturated or study populations so that the entire population were sampled. This research is correlational and ex post facto categorized. Questionnaire data collection techniques and documentation of learning achivement . The validity of the items were obtained from the product moment correlation. About the reliability of the formula obtained by alpha and declared reliable. Before the data were analyzed first tested the prerequisite analysis is normality test, multicollinearity, and linearity test. Analysis using partial correlation analysis and multiple regression analysis.From the analysis of the results obtained the following results: (1) There is a positive and significant relationship between vocational interest to learning (X1) with entrepreneurship interest (Y) on the studens Automotive Engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014; (2) There is a positive and significant relationship between entrepreneurial learning achivement (X2) with entrepreneurship interest (Y) on the studens Automotive Engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014; (3) There is a positive and significant relationship between vocational interest to learning (X1) and entrepreneurial learning achivement (X2) together withÂ  entrepreneurship interest (Y) on the studens Automotive Engineering Islamic Vocational School Yogyakarta Academic Year 2013/2014.